Motion chaos in the pseudoinverse control of redundant robots - Duarte, Fernando B. M. (2000)
When a manipulator is redundant it is anticipated that the inverse kinematics admits an infinitive number of solutions. Several kinematic control algorithms for redundant manipulators adopt generalized inverse matrices. In this line of thought, the generalized inverse control scheme is tested through experiments that reveal the difficulties that often arise. Motivated by these problems this paper studies kinematics and dynamics of the trajectory planning scheme. The experiment confirm the non-linear and chaotic performance of the algorithm and gives a deeper insight towards the future development of superior trajectory control systems.